Two-dimensional analysis of functionally graded thermoelastic microelongated solid - Sharma, Anchal; Ailawalia, Praveen (Zielona Góra: Uniwersytet Zielonogórski)
The present research focuses on two-dimensional deformation in a functionally graded thermoelastic micro-elongated medium. It is supposed that the non-homogeneous properties (thermal and mechanical) of FGM are in the x-direction. The normal mode technique is used to acquire the analytic expression for displacement components, stress, micro-elongation and temperature. The cause and effect relationship of non-homogeneity and physical quantities is shown through graphical results.
Keywords: functionally graded; thermoelastic; normal mode analysis; micro-elongation